Law and Development: Workers Welfare Based on the Principles of a Welfare State - Rehulina Rehulina (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The concept of a welfare state is a system of government that aims to improve the welfare and quality of life of its citizens, including basic needs such as health, education, housing, and social security. A welfare state seeks to reduce social and economic disparities through income redistribution and equitable fiscal policies. Workers play a key role in social welfare development. Employment is a vital issue for many people and ultimately reflects the level of progress of a country's development. Workers must earn a decent living. This aligns with the demands of a welfare state to protect the people from negative aspects. Indonesia, as a country that adheres to the principles of a welfare state, carries out national development, particularly in the development of quality human resources, such as workers. Workers must receive welfare guarantees from the state based on the principles of a welfare state. The problem is How is the government's effort in realizing the development of workers' welfare based on the principles of the welfare state? The research method used is normative juridical with secondary data sources. The government's efforts in realizing the development of workers' welfare based on the principles of the welfare state through laws and regulations, for example Law No. 40 of 2004 concerning the National Social Security System (SJSN), and institutions established by the state to realize workers' welfare in accordance with the principles of the welfare state. such as the Employment Planning and Development Agency (Barenbang), the Directorate General at the central level, the Manpower Office at the provincial and city/district levels, BPJS Employment, Technical Implementation Units (UPTD) such as the Job Training Center. The laws and regulations and institutions established with their respective institutional duties and responsibilities are realized through programs from each institution.